The Influence Of Honesty Cantine On Improvement Student Understanding About Anti-Corruption Values At SMPN 2 Cipunagara Subang (JED (Jurnal Etika Demokrasi), 2022)
The word corruption is covered almost every day by the mass media and has become a topic of discussion in various circles of society. Corruption is an extraordinary crime because it can affect the community, and in the long run, it is more dangerous for the younger generation's behavior. If conditions like that are allowed, the country's future will be very bleak. Therefore, it is necessary to instill anti-corruption values through education to internalize anti-corruption values in various ways, one of which is through the application of an honesty canteen. The purpose of this study was to determine the effect of the honesty canteen in increasing students' understanding of anti-corruption values at SMPN 2 Cipunagara. The method used is quantitative with descriptive verification method. The population is 391 students with a sample of 78 students. The approach used is quantitative with a descriptive verification method.Data collection techniques through questionnaires, interviews, observation, and document analysis. Data analysis relies on statistical tests of questionnaire results which are supported by interviews, observations, and document analysis. The results showed that the honesty canteen development model had a significant effect on the culture of anti-corruption values. This is evidenced by finding a correlation coefficient (r) of 0895 which means that the degree of relationship between variable X, namely honesty canteen, is very close and even perfectly related to variable Y, namely understanding anti-corruption values. The magnitude of the significance in the regression analysis is 0.174 > 0.05. The t value is 17.463 > t table 00003289 so it can be concluded that H1 is accepted, that is, there is an effect of X on Y. And the R-square value of 0.800 in the analysis of the coefficient of determination, which means the effect of X on Y is seen as 80 ,0%. This shows that the existence of honesty canteen activities in schools has a very positive impact on students' understanding of anti-corruption values.Kata korupsi hampir setiap hari diliput oleh media massa dan menjadi perbincangan di beragai kalangan masyarakat. Korupsi merupakan kejahatan yang tidak biasa (ekstra ordinary crime) karena dapat menimpa masyarakat dan  dalam jangka panjang lebih membahayakan perilaku generasi muda. Jika kondisi seperti itu dibiarkan masa depan suatu negara akan sangat suram. Oleh karena itu perlu dilakukan langkah-langkah menanamkan nilai-nilai antikorupsi melalui pendidikan untuk menginternalisasikan nilai-nilai antikorupsi dengan berbagai cara salah satunya melalui penerapan kantin kejujuran. Tujuan dari penelitian ini adalah untuk mengetahui pengaruh kantin kejujuran dalam meningkatkan pemahaman siswa tentang nilai-nilai antikorupsi di SMPN 2 Cipunagara. Metode yang digunakan adalah kuantitatif dengan metode deskriptif verifikatif. Populasi adalah 391 siswa dengan sampel 78 siswa. Pendekatan yang digunakan adalah kuantitatif dengan metode deskriptif verifikatif. Teknik pengumpulan data melalui kuesioner, wawancara, observasi, dan analisis dokumen.  Analisa data bertumpu kepada uji statistika hasil kuesioner yang didukung hasil wawancara, observasi, dan analisa dokumen. Hasil penelitian menunjukkan bahwa Model pengembangan kantin kejujuran berpengaruh signifikan terhadap budaya nilai-nilai anti korupsi. Hal ini diuktikan dengan ditemukannya koefisien korelasi (r) sebesar 0895 yang berarti bahwa derajat hubungan antara variael X yaitu kantin kejujuran sangat erat bahkan berhubungan  sempurna dengan variael Y yaitu pemahaman anti- nilai korupsi. Besarnya signifikansi dalam analisis regresi adalah  0,174 > 0,05  dan nilai t hitung 17.463 > t tabel 00003289 sehingga dapat disimpulkan bahwa H1 diterima yaitu terdapat pengaruh X terhadap Y. Dan nilai Rsquare sebesar 0.800 pada analisis koefisien determinasi yang berarti pengaruh X terhadap Y seesar 80,0%. Hal ini menunjukkanb bahwa adanya kegiatan kantin kejujuran di sekolah berdampak sangat  positif terhadap  pemahaman siswa terhadap nilai-nilai antikorupsi.